2012
DOI: 10.1088/0957-4484/23/4/045705
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of the tip–sample junction stability and image contrast reversal on a Cu(111) surface revealed by the 3D force field

Abstract: Non-contact atomic force microscopy is used to measure the 3D force field on a dense-packed Cu(111) surface. An unexpected image contrast reversal is observed as the tip is moved towards the surface, with atoms appearing first as bright spots, whereas hollow and bridge sites turn bright at smaller tip-sample distances. Computer modeling is used to elucidate the nature of the image contrast. We find that the contrast reversal is essentially a geometrical effect, which, unlike in gold, is observable in Cu due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
(57 reference statements)
2
24
0
Order By: Relevance
“…The challenges of atomic point contacts have been addressed by various approaches, including the break-junction method [2][3][4][5], transmission electron microscopy [6], and scanning tunneling microscopy (STM) [7][8][9][10][11][12][13][14][15], as well as in theoretical calculations [16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges of atomic point contacts have been addressed by various approaches, including the break-junction method [2][3][4][5], transmission electron microscopy [6], and scanning tunneling microscopy (STM) [7][8][9][10][11][12][13][14][15], as well as in theoretical calculations [16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…The histograms taken on metals, except noble ones, exhibit broad distributions with multiple peaks, which have been attributed to the stochastic nature of the contact formation. In fact, theoretical studies have indicated that the lateral configuration of the contact-forming atoms causes this significant variation in conductance [16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…(b) Utilizing an alternative approach, the volumetric f (x, y, z) data may be recorded in a layer-by-layer fashion, by combining a group of topographical NC-AFM images that contain f (x, y) data for set tip-sample distances z [26,29,31,32,36]. Volumetric maps of interaction force (F(x, y, z)) and energy (E(x, y, z)) are then obtained via the same procedures employed for the curveby-curve approach [22].…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Additionally, contrast changes with respect to changing tip-sample distance (such as those in [26,32]) are directly observed during data acquisition, while such information only becomes observable after data processing in the case of curve-by-curve data acquisition.…”
Section: Comparison Of Data Acquisition and Processing Strategies Formentioning
confidence: 99%
See 1 more Smart Citation